Customized Employment: A Systematic Approach To Community Integration And Strategies To Obtain Competitive Employment - Edeiken_Cooperman, Nanette (Advances in Social Sciences Research Journal, 2017)
The purpose of this qualitative, multimethod study was to investigate the role of an agency that implements a systematic planning approach to assisting individuals with disabilities to integrate into the community and to obtain competitive or customized employment. The agency that was part of this study has implemented the philosophy of Employment First and has found that the experience of customized employment maximizes the independence and self-determination of the individual while at the same time promoting a positive self image. Data was collected using semi-structured interviews and direct non-participant and participant observations with the intent to exemplify that customized employment is a successful, alternate strategy for job seekers with significant disabilities when the demands of integrated employment become a barrier. The results revealed that a national initiative related to Employment First is a necessity in order to promote the successful employment of all individuals with disabilities earning minimum wage or higher.